High Prevalence of Humoral and Cellular Immunity to Influenza Viruses in Preschool Children Living in Addis Ababa, Ethiopia. (11th February 2017) - Dembinski, Jennifer L.; Mihret, Adane; Yimer, Solomon A.; Tessema, Bamlak; Trieu, Mai-Chi; Tarekegn, Azeb; Getachew, Nahom; Cox, Rebecca J.; Oftung, Fredrik; Haneberg, Bjørn; Aseffa, Abraham; Mjaaland, Siri
Abstract: Background: Influenza in children who reside in tropical and subtropical regions has until recently been regarded as insignificant. However, new evidence suggests that it significantly impacts hospitalization and promotes secondary bacterial coinfections. Ethiopia is situated in a subtropical area where influenza viruses are likely to circulate year round. Methods: Clinical data were recorded in a cohort of 103 healthy preschool children recruited in Addis Ababa, Ethiopia. Humoral and cellular immune responses to influenza virus were determined by hemagglutination inhibition (HI) and interferon-γ enzyme-linked immunospot assays. Results: Ninety-six percent of the children (2–5 years old) had pre-existing HI antibody responses to 1 or more of the circulating influenza A subtypes, H1N1 (51%), H3N2 (86%), or influenza B (51%) strains. At the age of 4, all children had been infected with at least 1 strain, and 75% had been infected with 2–4 different viral strains. CD4 + and CD8 + T-cell responses against conserved viral antigens increased with repeated exposures, indicating boosting of cross-reactive cellular immunity. Malnutrition did not seem to affect these immune responses to influenza. Conclusions: Influenza is highly prevalent among children in this area of Ethiopia. Due to the risk of secondary bacterial pneumonia, increased influenza awareness might benefit child health.